Common breeding sites surrounded in the region of the araucaria forests - Campigoto, José Adilçon (Seven Editora, 2023)
Investigations in the area of the history of traditional peoples, specifically of the faxinalenses, tend to the scope of the present time, either because of the emphasis on the aspect of territorialities, or due to the lack of written documents that go beyond the field of memories and images. For this reason, we suppose, it has been difficult to understand the collective fence that surrounds the common breeding facilities located in cleaning areas, as an event restricted to a region of the current state of Paraná. We investigate how this distinct way of organizing the relations between the chamber of humans and that of nonhumans was constituted. It is assumed that, due to the model of occupation of the Brazilian territory by the Portuguese, the rocios served as a certain pattern to the common breeding sites surrounded by the sharing of the inhabited space between domestic animals and human beings. As the elevation of the parishes to the category of villages marks the beginning of the local legislation regarding the use of the rocios, and the terms of the municipalities, the documentary body of this project is constituted by these legislations. Curitiba because it is an important urban center in which communities are organized in the form of faxes in the area of metropolitan coverage will have centrality in terms of spatial cut. DOI:https://doi.org/ 10.56238/devopinterscie-223